2020
DOI: 10.1186/s12866-020-01851-2
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of tomato bacterial wilt by the new strain Bacillus velezensis FJAT-46737 and its lipopeptides

Abstract: Background: There is an urgent need to discover biocontrol agents to control bacterial wilt. This study reports on a new lipopeptide-producing biocontrol strain FJAT-46737 and explores its lipopeptidic compounds, and this study investigates the antagonistic effects of these compounds. Results: Based on a whole genome sequence analysis, the new strain FJAT-46737 was identified as Bacillus velezensis, and seven gene clusters responsible for the synthesis of bioactive secondary metabolites in FJAT-46737 were pred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 50 publications
2
47
1
3
Order By: Relevance
“…Several synthetic fungicides have been used by farmers for the control of early blight of Tomato [42]. But, due to their continuous usage and also non-adherence to prescribed dosages, resistance build-upof resistance has been observed [43] [21,50]. This research articles is the rst report of a B. velezensis strain isolated from major tomato growing regions of Tamil Nadu, India which is effective against A. solani.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several synthetic fungicides have been used by farmers for the control of early blight of Tomato [42]. But, due to their continuous usage and also non-adherence to prescribed dosages, resistance build-upof resistance has been observed [43] [21,50]. This research articles is the rst report of a B. velezensis strain isolated from major tomato growing regions of Tamil Nadu, India which is effective against A. solani.…”
Section: Discussionmentioning
confidence: 99%
“…Among Bacillus spp., B. velezensis is one of the potential biocontrol agent [19,20]. Literature reports numerousstrains of B. velezensis strains capable of controlling the major plant pathogens (bacteria & fungi) and nematodes [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus simplex 30N-5 and Bacillus subtilis 30VD-1 can inhibit growth of Fusarium spp. Chen et al [16] reported B. velezensis FJAT-46737 as potential biocontrol agent for Fusarium oxysporum.…”
Section: Antagonistic Activity Assaymentioning
confidence: 99%
“…B. velezensis strains are known as biological control agents that suppress certain dangerous plant diseases caused by R. solanacearum on tomato (Chen et al, 2020), Fusarium graminearum on corn (Wang et al, 2020), and Botrytis cinerea on strawberry (Toral et al, 2020). In addition to biocontrol, B. velezensis strains may promote plant growth (Fan et al, 2018;Myo et al, 2019;Torres et al, 2020).…”
Section: Introductionmentioning
confidence: 99%